A foresight study on green technology in paint industries in Malaysia - Ramasamy, Chandrashekar; Mohan, Kanchana; Shamsuddin, Alina (American Scientific Publishers, 2018)
Green technology paint industries have been rising significantly over the years due to its benefit to environment and consequently to human health. However, the high manufacturing cost and other disadvantages threatened its sustainability in the future. Therefore a research was carried out to identify the issues and drivers of employing in green technology paint industries and to study the future trend of green technology paints in Malaysia. STEEPV approach which is an acronym for (Social, Technological, Environmental, Economic, Political and Values) is an internationally recognized tool used in conducting technology foresight worldwide. This tool was used in the current research in identifying various issues and drivers based on the above mentioned six categories. New technologies in preparing low energy consuming paints and the role of government and non-governmental organization was voted as the most influential drivers for the eco-friendly paint industries in Malaysia. In line with this regard, a scenario development carried out and a number of projects were suggested in order to move towards sustainable development of eco-friendly paint industry. As a consequence it is recommended to add more political will and support in such projects to ensure the ownership at the top level and maximize the chances of implementing the outcomes.